NATURAL CATI2O4-STRUCTURED FECR2O4 POLYMORPH IN THE SUIZHOU METEORITE AND ITS SIGNIFICANCE IN MANTLE MINERALOGY - Chen M.; Shu J.; Xie X.; Mao H.K. (My University, 2003)
The first natural occurrence of a high-pressure polymorph of chromite has been discovered in the shock-metamorphosed Suizhou meteorite. The composition of this high-pressure polymorph is identical to that of the precursor chromite. The Raman spectrum of this polymorph is distinct from that of chromite. Synchrotron X-ray diffraction analysis revealed that this polymorph has an orthorhombic CaTi2O4- type structure. The cell parameters are: a = 9.462(6) A, b = 9.562(9) A, c = 2.916(1) A, V = 263.8(4) A3 (Z=4), space group = Bbmm, and the density = 5.63 g/cm3 (the numbers in parentheses are standard deviations on the last significant digits). This polymorph is 11.5% denser than chromite. The P-T conditions for the phase transformation from chromite to the CaTi2O4-structured polymorph are estimated at 20-23 GPa and 1800 to 2000 °C, respectively. This dense CaTi2O4-structured FeCr2O4 phase could be a host phase for Cr, Al, Fe, Mg and Mn and other metallic elements in the deep Earth.